Analisis Peluang dan Ancaman Perdagangan Produk Perikanan Bernilai Tinggi serta Kebijakan Keamanan Pangan: Studi Kasus Indonesia dan Jepang dalam Kerangka APEC - Dede Fitriya; Daspar (CV. ITTC INDONESIA, 2025)
The international trade of high-value fishery products plays a vital role in the economic relationship between Indonesia and Japan, particularly within the framework of the Asia-Pacific Economic Cooperation (APEC). Commodities such as tuna, crab, and shrimp are among Indonesia’s top export products to Japan, with demand increasing due to the healthy food trend. However, challenges arise from stringent food safety standards, tariff and non-tariff barriers, and risks of product quality mismatch. Through policy analysis and trade trend evaluation, this study examines the opportunities and threats in the trade of high-value fishery products and highlights the importance of harmonizing food safety regulations to enhance Indonesia’s competitiveness in the Japanese market.